Biologically active phthalocyanine metal complexes: Preparation, evaluation of α-glycosidase and anticholinesterase enzyme inhibition activities, and molecular docking studies - Guzel, Emre; Kocyigit, Umit M.; Taslimi, Parham; Erkan, Sultan; Taskin, Omer S.; Taslimi, Parham (Wiley, 2021)
In this study, preparation, as well as investigation of alpha-glycosidase and cholinesterase (ChE) enzyme inhibition activities of furan-2-ylmethoxy-substituted compounds 1-7, are reported. Peripherally, tetra-substituted copper and manganese phthalocyanines (5 and 6) were synthesized for the first time. The substitution of furan-2-ylmethoxy groups provides remarkable solubility to the complex and redshift of the phthalocyanines Q-band. Besides, the inhibitory effects of these compounds on acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and alpha-glycosidase (alpha-Gly) enzymes have been investigated. The AChE was inhibited by these compounds (1-7) in low micromolar levels, and K-i values were recorded between 11.17 +/- 1.03 and 83.28 +/- 11.08 mu M. Against the BChE, the compounds demonstrated K-i values from 7.55 +/- 0.98 to 81.35 +/- 12.80 mu M. Also, these compounds (1-7) effectively inhibited alpha-glycosidase, with K-i values in the range of 744.87 +/- 67.33 to 1094.38 +/- 88.91 mu M. For alpha-glycosidase, the most effective K-i values of phthalocyanines 3 and 6 were with K-i values of 744.87 +/- 67.33 and 880.36 +/- 56.77 mu M, respectively. Moreover, the studied metal complexes were docked with target proteins PDB ID: 4PQE, 1P0I, and 3WY1. Pharmacokinetic parameters and secondary chemical interactions that play an active role in interaction were predicted with docking simulation results. Overall, furan-2-ylmethoxy-substituted phthalocyanines can be considered as potential agents for the treatment of Alzheimer's diseases and diabetes mellitus.
Keywords: Cholinesterases; Enzyme Inhibition; Molecular Docking; Phthalocyanine; ? - Glycosidase